Digital liaisons virtual uncommons: Connecting information and people in order to enhance lives via digital librarianship. Issue 1 (24th October 2017) - Cunningham, Chris; Dressler, Virginia; Grguric, Ekatarina; Gamble, Alyson; Khan, Nushrat
ABSTRACT: Digital librarianship is a rich space in which new practitioners often find their feet on the job, picking up needed skill sets and adapting to new technologies on the fly. Creating a space for peer information sharing and mentorship is particularly important for this community. Virtual chat sessions and unconferences are two innovative ways to connect established practitioners with less experienced students and professionals in supportive, collaborative environments. By combining these two formats, it is possible to create a more inclusive space for mentorship and peer information sharing. We propose hosting a virtual uncommons that transcends geographical locations and other physical barriers. The digital liaisons virtual uncommons (DLVU) will feature leaders in digital libraries who will act in a mentoring capacity by responding to questions posed by new information professionals throughout a series of virtual chat sessions and an in‐person unconference session. In the DLVU, students and early career professionals will be able to connect with peers and mentors in the field of digital librarianship. The virtual uncommons will be a space for informal mentoring and serendipitous networking. This session will be composed of a series of Twitter chats under the hashtag #SIGDLchats and a reflective panel structured as an attendee driven unconference in which panelists serve as moderators.